The limitations of in vitro experimentation in understanding biofilms and chronic infection - Roberts, Aled; Kragh, Kasper; Bjarnsholt, Thomas; Diggle, Stephen P. (Elsevier, 2015)
We have become increasingly aware that during infection, pathogenic bacteria often grow in multi- cellular biofilms which are often highly resistant to antibacterial strategies. In order to understand how biofilms form and contribute to infection, in vitro biofilm systems such as microtitre plate as- says and flow cells, have been heavily used by many research groups around the world. Whilst these methods have greatly increased our understanding of the biology of biofilms, it is becoming increasingly apparent that many of our in vitro methods do not accurately represent in vivo conditions. Here we present a systematic review of the most widely used in vitro biofilm systems, and we discuss why they are not always representative of the in vivo biofilms found in chronic infections. We present examples of methods that will help us to bridge the gap between in vitro and in vivo biofilm work, so that our bench-side data can ultimately be used to improve bedside treatment.